Chromogenic assay for BAY 81‐8973 potency assignment has no impact on clinical outcome or monitoring in patient samples. (3rd May 2016) - Kitchen, S.; Katterle, Y.; Beckmann, H.; Maas Enriquez, M.
Abstract : Essentials Discrepancies can exist in factor VIII activity measured by the one‐stage or chromogenic assays. LEOPOLD trial data were used to assess clinical impact of BAY 81‐8973 potency assignment assay. Efficacy was not affected by the assay used for potency assignment and dosing of BAY 81‐8973. Either assay may be used to measure factor VIII activity after BAY 81‐8973 infusion. Summary: Background: Product‐specific discrepancies have been reported for factor VIII (FVIII) activity determined with one‐stage or chromogenic assays. Objective: To assess the clinical impact of potency assignment of BAY 81‐8973, a full‐length, unmodified, recombinant human FVIII, by use of the chromogenic assay or chromogenic assay adjusted to mimic results obtained with the one‐stage assay Patients/methods: Patients aged 12–65 years with severe hemophilia A received BAY 81‐8973 in LEOPOLD I (20–50 IU kg −1 two or three times weekly [investigator decision]) and LEOPOLD II (randomized to 20–30 IU kg −1 twice weekly, 30–40 IU kg −1 three times weekly, or on‐demand treatment). Both trials included two 6‐month crossover periods in which potency labeling was determined with the chromogenic substrate assay as per the European Pharmacopoeia (CS/EP) or the chromogenic substrate assay adjusted to mimic results obtained with the one‐stage assay (CS/ADJ). The annualized bleeding rate (ABR) and FVIII incremental recovery were assessed by the use of pooled data. Results: The analysis was perfomed on 121 patients. Median (quartile [Q] 1; Q3) ABRs during the CS/EP and CS/ADJ periods were 1.98 (0; 5.92) and 1.98 (0; 7.34), respectively. The mean incremental recovery was > 2 IU dL −1 per IU kg −1 in both periods with the use of either assay for postinfusion FVIII measurements. The median (Q1; Q3) chromogenic/one‐stage assay recovery ratio was 1.054 (0.892; 1.150) for the CS/EP period when a plasma standard was used for calibration. Conclusions: No impact on the ABR was observed with chromogenic‐based as compared with one‐stage assay‐based potency and dosing. Either assay may be used to determine FVIII plasma activity after infusion of BAY 81‐8973 without the need for a product‐specific standard.